2007
DOI: 10.1897/06-595r.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal evaluation of metal concentrations in soils and sediments from new orleans, louisiana, USA, following hurricanes Katrina and Rita

Abstract: During January 2006, soil and sediment samples from 75 sites in the New Orleans (LA, USA) area were collected and tested for 26 inorganic elements. The study design was intended to provide a spatial pattern of metal concentrations within the city following hurricanes Katrina and Rita. The sampling design included four transects that traversed the city in a north-south direction and three transects that traversed the city in an east-west direction. Contaminant concentrations were determined at multiple sites wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The study by Wang et al (2004) identified Pb concentrations in soil ranging from 31.7 to 5,195 lg/g, with an arithmetic mean of 784 lg/g (Wang et al 2004). For comparison purposes, Pb concentrations detected in our study of New Orleans soils (Abel et al 2007) ranged from 7.72 to 8,550 lg/g, with an arithmetic mean of 272 lg/g. Furthermore, a comprehensive effort from Xavier University provided two sweeping surveys for multiple metal accumulation in New Orleans soil.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The study by Wang et al (2004) identified Pb concentrations in soil ranging from 31.7 to 5,195 lg/g, with an arithmetic mean of 784 lg/g (Wang et al 2004). For comparison purposes, Pb concentrations detected in our study of New Orleans soils (Abel et al 2007) ranged from 7.72 to 8,550 lg/g, with an arithmetic mean of 272 lg/g. Furthermore, a comprehensive effort from Xavier University provided two sweeping surveys for multiple metal accumulation in New Orleans soil.…”
Section: Discussionmentioning
confidence: 53%
“…Based on this finding, we continued investigating surficial soils throughout New Orleans, focusing particularly on Pb contamination (Abel et al 2007;Cobb et al 2006). It was determined that Pb concentrations intermittently exceeded the EPA soil screening criteria for human health throughout the city.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial exposure to toxic metals accelerates development of bacterial resistance to antibiotics 13, which could pose public health concerns. Subsequent research determined that contaminants were elevated in marshes near pumping stations 8 and that metal contamination of soils was widespread in greater New Orleans 14–17. Furthermore, available fractions of metals substantiated the potential for human and ecological health risks 15, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were prepared using US EPA method 3050 B and analyzed according to US EPA method 6010 B [26][27][28][29]. A thorough explanation of the sampling, preparation, analysis, reporting and moisture-corrected results are available in Abel et al [14]. To expand the data set, we included the Pb concentration data collected by Suedel et al [16] from Violet Marsh, an undeveloped area directly northeast of the ninth ward, with our Pb concentration data from metropolitan New Orleans to create a more thorough spatial distribution map.…”
Section: Methodsmentioning
confidence: 99%
“…Following hurricanes Katrina and Rita, several government agencies and academic institutions, including United States Geological Survey (USGS), United States Environmental Protection Agency (USEPA), United States Army Corps of Engineers (USACE), Louisiana State University (LSU), Tulane University (TU), University of Missouri-Rolla, and Texas Tech University (TTU), evaluated the environmental impact of the hurricanes on New Orleans, LA [9][10][11][12][13][14][15][16]. Each institution reported elevated occurrences of Pb in soil, sediment, or water.…”
Section: Introductionmentioning
confidence: 99%